Inter-Continental Concerts: 8th EuPRA Conference - Sam, Mosallaeipour; Shahed, Mohsenizonoozi (http://intercontinentalconcerts.org, 2013)
[Abstract Not Available]
Keywords: EuPRA Conference; Intercontinental Concerts; Sam Mosallaeipour; Shahed Mohseni Zonoozi; EuPRA; Conference